The "too big to fail" subsidy in Canada: Some estimates - Patricia Palhau Mora (Bank of Canada, 2018)
Implicit government guarantees of banking-sector liabilities reduce market discipline by private sector stakeholders and temper the risk sensitivity of funding costs. This potentially increases the likelihood of bailouts from taxpayers, especially in the absence of effective resolution frameworks. Estimates of "too big to fail" (TBTF) implicit subsidies are useful to understand bank agents' incentives, measure potential resolution costs and assess the credibility of regulatory reform. Given the implicit nature of the subsidy, I propose a framework that adopts two empirical approaches to assess the quantum of the subsidies accruing to systemic banks in Canada. The first is based on credit rating agencies' assessment of public support and the second relies on a contingent claims analysis. Results suggest more progress on resolution is needed, such as the implementation of a credible statutory bail-in regime for senior obligations, to increase market discipline and help address TBTF externalities. That said, Canada being an early adopter of Basel III might help explain the significant reduction in the government's contingent liability since the peak years of the crisis.
Keywords: G13; G21; G28; 330; Financial institutions; Financial stability